Nurses' Attitudes and Behaviors Towards Nosocomial Infection Prevention - Anggeraeni Anggeraeni; Hairuddin K; Nordianiwati Nordianiwati; Cyntia Theresia Lumintang (Jurnal Edukasi Ilmiah Kesehatan, 2023)
Background: Health services require health workers who are devoted to every field of health and have the knowledge and skills in the health sector to carry out health efforts. Health workers perform their obligations and duties must be based on licenses and rules that the hospital has determined. Purpose: Knowing the attitude and behavior of nurses towards preventing Nosocomial infections. Method: Descriptive research design using cross-sectional study design. There were 75 samples with a total sampling technique. Results: This showed that nurse attitudes for all nurses had a positive attitude of 75 respondents and negative behavior of 1 respondent. Conclusion: The whole nurse has a positive attitude towards preventing nosocomial infections. Factors associated with nosocomial infections are invasive tinting and infusion insertion, overcrowded room, misuse of antibiotics, improper sterilization procedures, and non-observance of infection control regulations by nurses